Telemedicine in stroke patients during the COVID-19 pandemic: Literature Review - Pradani, Indra; Sulistyani, Sulistyani (International Journal of Health Science and Technology, 2023)
The effectiveness of stroke therapy depends on speed, accuracy and a multidisciplinary approach. The era of the COVID-19 pandemic has caused a high risk of treatment for stroke patients. The application of telemedicine or telestroke that is good and focuses on quality is a possible alternative for stroke therapy during the COVID-19 pandemic. This study aims to determine the effectiveness of telemedicine in stroke patients during the COVID-19 pandemic. This study used a systematic review research design, namely by searching journal articles on Google Scholar, PubMed, and Research Gate databases, using keywords ("Telemedicine" OR "Tele stroke") AND ("stroke" OR "strokes" OR "cerebrovascular accident" OR "cerebral stroke") AND ("COVID 19" OR "COVID-19 Virus Disease" OR COVID19 OR "Coronavirus disease 2019").  Based on searching and searching for journal articles in 2019 - 2021, 131 journals were obtained from PubMed, 90 journals from ResearchGate, and 1000 journals from Google Scholar.  A total of 1221 journals were obtained, and 8 scientific articles fit the inclusion criteria. It can be concluded that the application of telemedicine in stroke patients during the COVID-19 pandemic has been implemented in various countries with evidence that it can reduce comorbidities, improve clinical outcomes, and reduce the recurrence of stroke patients. Telemedicine can be applied to stroke patients with clear diagnosis criteria, a multidisciplinary approach, and a complete infrastructure.